2016
DOI: 10.1016/j.childyouth.2016.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Financial well-being in family-based foster care: Exploring variation in income supports for kin and non-kin caregivers in California

Abstract: Kinship foster parents have the same responsibilities as nonrelative foster parents and are held to the same standards of rehabilitative care. Nonetheless, their rights to financial supports and their access to other services vary across states depending on the federal eligibility of the child, and/or the licensing criteria caregivers may or may not meet. We know little about the financial supports, well-being, or services of kinship caregivers receiving differential payment schemes and whether or not these fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Specifically, single parents often report more emotional and financial strain than partnered caregivers (Glass et al, 2016), and single-parent households are more likely to experience poverty than twoparent households (e.g., Goodrum et al, 2012). In addition, grandparent and other relative caregivers have also reported higher levels of financial constraint compared to non-relative foster parents (Berrick & Boyd, 2016). Findings from this study indicate that those with less financial insecurity are more likely to report higher levels of stress during COVID-19.…”
Section: Current Financial Statusmentioning
confidence: 66%
“…Specifically, single parents often report more emotional and financial strain than partnered caregivers (Glass et al, 2016), and single-parent households are more likely to experience poverty than twoparent households (e.g., Goodrum et al, 2012). In addition, grandparent and other relative caregivers have also reported higher levels of financial constraint compared to non-relative foster parents (Berrick & Boyd, 2016). Findings from this study indicate that those with less financial insecurity are more likely to report higher levels of stress during COVID-19.…”
Section: Current Financial Statusmentioning
confidence: 66%
“…Kinship families are characterized as having financial strain and receiving limited financial assistance from the government (Berrick & Boyd, 2016; Murray et al, 2004). No previous studies have examined the relationships between economic well-being and children’s behavioral health outcomes in kinship care.…”
Section: Economic Well-being and Children’s Behavioral Health Outcomesmentioning
confidence: 99%
“…Kinship families are usually underserved financially, particularly compared to nonrelative FC providers. For instance, Berrick and Boyd (2016) have indicated that 25.6% fewer kinship foster parents receive FC subsidies than nonrelative foster parents, less than one fourth (12.0%–23.8%) of kinship foster parents receive TANF family or child-only grants, and a range of kinship foster caregivers (4.0%–34.3%) do not receive any subsidies.…”
Section: Financial Assistance For Kinship Familiesmentioning
confidence: 99%
“…As noted elsewhere, similarly situated children living with relative caregivers have access to different kinds of supports and services, depending upon their legal relationship to their caregiver (Berrick & Boyd, 2016; Berrick & Hernandez, 2016). This is in spite of the fact that typical kinship caregivers display a high degree of need for material and caregiving supports (Smithgall, DeCoursey, & Goerge, 2008; Zinn, 2009).…”
Section: Discussionmentioning
confidence: 99%